The Intriguing Connection Between the Gut and Lung Microbiomes - Magdalena Druszczynska; Beata Sadowska; Jakub Kulesza; Nikodem Gąsienica-Gliwa; Ewelina Kulesza; Marek Fol (Pathogens)
Recent advances in microbiome research have uncovered a dynamic and complex connection between the gut and lungs, known as the gut–lung axis. This bidirectional communication network plays a critical role in modulating immune responses and maintaining respiratory health. Mediated by immune interactions, metabolic byproducts, and microbial communities in both organs, this axis demonstrates how gut-derived signals, such as metabolites and immune modulators, can reach the lung tissue via systemic circulation, influencing respiratory function and disease susceptibility. To explore the implications of this connection, we conducted a systematic review of studies published between 2001 and 2024 (with as much as nearly 60% covering the period 2020–2024), using keywords such as “gut–lung axis”, “microbiome”, “respiratory disease”, and “immune signaling”. Studies were selected based on their relevance to gut–lung communication mechanisms, the impact of dysbiosis, and the role of the gut microbiota in respiratory diseases. This review provides a comprehensive overview of the gut–lung microbiome axis, emphasizing its importance in regulating inflammatory and immune responses linked to respiratory health. Understanding this intricate pathway opens new avenues for microbiota-targeted therapeutic strategies, which could offer promising interventions for respiratory diseases like asthma, chronic obstructive pulmonary disease, and even infections. The insights gained through this research underscore the potential of the gut–lung axis as a novel target for preventative and therapeutic approaches in respiratory medicine, with implications for enhancing both gut and lung health.